Zonula Occludens-1 Alters Connexin43 Gap Junction Size and Organization by Influencing Channel Accretion - Hunter, Andrew W. (The American Society for Cell Biology, 2005)
Regulation of gap junction (GJ) organization is critical for proper function of excitable tissues such as heart and brain, yet mechanisms that govern the dynamic patterning of GJs remain poorly defined. Here, we show that zonula occludens (ZO)-1 localizes preferentially to the periphery of connexin43 (Cx43) GJ plaques. Blockade of the PDS95/dlg/ZO-1 (PDZ)-mediated interaction between ZO-1 and Cx43, by genetic tagging of Cx43 or by a membrane-permeable peptide inhibitor that contains the Cx43 PDZ-binding domain, led to a reduction of peripherally associated ZO-1 accompanied by a significant increase in plaque size. Biochemical data indicate that the size increase was due to unregulated accumulation of gap junctional channels from nonjunctional pools, rather than to increased protein expression or decreased turnover. Coexpression of native Cx43 fully rescued the aberrant tagged-connexin phenotype, but only if channels were composed predominately of untagged connexin. Confocal image analysis revealed that, subsequent to GJ nucleation, ZO-1 association with Cx43 GJs is independent of plaque size. We propose that ZO-1 controls the rate of Cx43 channel accretion at GJ peripheries, which, in conjunction with the rate of GJ turnover, regulates GJ size and distribution.